Kategori Studi dan Kesenjangan Pengetahuan di Literatur Standar dan Sertifikasi Kopi Berkelanjutan - Muhammad Ibnu (AGRIMOR, 2023)
Sustainability standards and certification have been a trend in the coffee trade in the international market. Established based on the premise of the Theory of Change, sustainable standards and certification aim to improve the sustainability of the coffee sector, both economically, socially and environmentally. This article is a scientific review that summarizes and analyzes the results of studies on sustainable standards and certification. The literature on sustainability standards and certification is quite rich with studies conducted in coffee-producing countries in Asia, Africa, and Latin America. The aim of this paper is to categorize these studies by theme and, based on the existing knowledge gap, also provide recommendations for future research. The results of the review found that the majority of studies were conducted using macro and managerial approaches, and there is still a knowledge gap in the literature. It is necessary to change the approach in future studies to address this knowledge gap. Further research is recommended to use micro-level analysis and a bottom-up perspective (based on farmers’ perspective) to generate empirical knowledge on the social, economic, and environmental aspects of sustainability standards and certification.